Effect of Profitability, Leverage and Capital Intensity on Tax Aggressiveness Moderated Market Performance - Maulana Yusuf; Lestari Manurung; Aris Riantori Faisal; Murtanto Murtanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of profitability, leverage, and capital intensity on tax aggressiveness with market performance as a moderating variable. The dependent variable is tax aggressiveness, while the independent variables are profitability, leverage and capital intensity, which are moderated by performance. The population of this study uses property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method used is purposive sampling with certain criteria. The type of data used is secondary data. Data analysis used panel data regression analysis with moderated regression analysis using software eviews 10. The results showed that profitability had no significant effect on tax aggressiveness, leverage had no significant effect on tax aggressiveness, capital intensity had a significant effect on tax aggressiveness, market performance moderated the effect between profitability, leverage and capital intensity on tax aggressiveness. The novelty of this research is adding a moderating variable of market performance. The variable of tax aggressiveness is influenced by the independent variable by 23.4%.